Identification and study of lipid metabolism genes by qPCR in Rubisco mutants of Chlamydomonas reinhardtii - Gaspar, Miguel Camões Fragoso (2018)
Tese de mestrado em Biologia Molecular e Genética, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2017